Technical exercises for the improvement of the shot on goal in U12 players/Los ejercicios técnicos para la mejora del tiro a portería en futbolistas sub 12 - Carlos Eduardo Alba Cajamarca (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The suspension of sports training due to the health emergency caused by COVID 19 has led to the search for alternatives to counteract training in this context. The objective of this research consisted of presenting a proposal for the contextualization of exercises at home to improve shots on goal, in adolescent athletes with ludic guidelines. The methodology used was the phenomenological-hermeneutic, with which we want to describe and interpret the experience of ten soccer coaches of minor divisions, from different teams of the neighborhood leagues in the city of Quito. For this, the interview technique was applied through the question bank instrument, which responded to two dimensions: the first, the system of specific exercises for the type of goalkeeping and the second, the playful approach in the realization of exercises.  The results of the interviews were analyzed and synthesized into two components: the first was the ludic approach in the realization of exercises, where the design of ludic activities stands out, and the second component was the system of specific exercises for the goal type. It was possible to obtain a contextualized proposal to the circumstances experienced by adolescent athletes and their difficulties in sports training, suggesting the inclusion of the ludic approach, the use, adaptation and creation of sports implements and their applicability in different spaces, all this with the practice of specific technical contents for the improvement of the shot to goal, in the context of the pandemic.